Bogs and Fens in the Hudson Bay Lowlands - Sjörs, Hugo (ARCTIC, 1959)
Describes structural and vegetative features of bogs and fens in the peatlands area south and west of Hudson Bay, examined in summer 1957 mainly near the confluence of the Attawapiskat and Muketei Rivers (approx. 53 N, 86 W). Distinctive features of the ridge-shaped raised bogs are their undulating surfaces, large shallow pools, and lateral seepages (small, shallow pools termed flarks, in a stepped arrangement down the bog edges). Bog vegetation, typical of ombrotrophic peatlands, is acidophilous and low in pH value except in limited areas, e.g. fissures caused by frost heaving where fen plants are found, also the lateral seepages where patches of true fen vegetation appear along the rows of flarks. The plant communities are almost identical with those of similar raised bogs in Sweden and Finland. Fen surfaces are covered by large pools, and alternating low ridges low ridges and flarks. The fen water is highly minerotrophic, resulting in vegetation richer in mineral nutrients than that of the bogs, and similar to the "rich fen" or "brown fen" vegetation of Scandinavia. Roundish "black-spruce islands" are conspicuous fen features; they have permafrost cores as do knolls (palsas) north eastward near Sutton and Hawley Lakes.